2020
DOI: 10.3390/ani10091565
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Reveals the Expression Profiles of Long Non-Coding RNAs in Lactating Mammary Gland from Two Sheep Breeds with Divergent Milk Phenotype

Abstract: Long non-coding RNAs (lncRNAs) are a kind of non-coding RNA with >200 nucleotides in length. Some lncRNAs have been proven to have clear regulatory functions in many biological processes of mammals. However, there have been no reports on the roles of lncRNAs in ovine mammary gland tissues. In the study, the expression profiles of lncRNAs were studied using RNA-Seq in mammary gland tissues from lactating Small-Tailed Han (STH) ewes and Gansu Alpine Merino (GAM) ewes with different milk yield and ingredients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Further enrichment analysis of the candidate genes revealed that they were categorized into 127 GO categories and 82 signaling pathways, from which we selected two GO entries and seven signaling pathways. Previous studies have demonstrated an association between animal milk fat synthesis and the ubiquitination pathway, insulin (PI3K-Akt) pathway, Wnt signaling pathway, and mTOR signaling pathway [ 45 – 47 , 49 , 50 ]. Animal milk yield is closely linked to GnRH secretion, the MAPK signaling pathway, and the FoxO signaling pathway [ 43 , 48 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further enrichment analysis of the candidate genes revealed that they were categorized into 127 GO categories and 82 signaling pathways, from which we selected two GO entries and seven signaling pathways. Previous studies have demonstrated an association between animal milk fat synthesis and the ubiquitination pathway, insulin (PI3K-Akt) pathway, Wnt signaling pathway, and mTOR signaling pathway [ 45 – 47 , 49 , 50 ]. Animal milk yield is closely linked to GnRH secretion, the MAPK signaling pathway, and the FoxO signaling pathway [ 43 , 48 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genes enriched in these pathways were also considered candidate genes (Fig. 5F) [46][47][48][49][50].…”
Section: Functional Enrichment Analysismentioning
confidence: 99%
“…Although these studies have explored the expression profile of sheep’s mammary gland during different stages of lactation, little is known about the underlying mechanisms that render the mammary gland highly productive or not within breed in terms of milk yield. To this end, research on the expression profiles of long non-coding RNAs (lncRNAs) ( Hao et al, 2020a ) and circular RNA (circRNA) ( Hao et al, 2020b ) in the mammary gland of ewes of different performances has been conducted, investigating the interactions within the lncRNAs-mRNA and circRNA-miRNA networks, respectively, in relation to milk synthesis and mammary gland development.…”
Section: Introductionmentioning
confidence: 99%